Brookfield Congregational Church, general view, Brookfield, Massachusetts, 2 of 3. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of the Brookfield Congregational Church. Built in 1857. Church is located on 8 Central Street, Brookfield, Massachusetts. An example of the Italianate Revival. Slide 2 of 3.; Caption on image: Church (2) Ext, gen. view.; Binder Number 4. Pocket Number: 2.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.